SINERGITAS PEMERINTAH KOTA PEKANBARU DALAM MENINGKATKAN KETERSEDIAAN PANGAN TAHUN 2021-2024 - Fifi Amalia; Rico Purnawandi Pane (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
Food security is a strategic issue that concerns the fulfillment of basic human rights and the sustainability of development. Food availability constitutes the first pillar in the food security system, emphasizing the extent to which food is sufficiently available to meet community needs. This research is motivated by the importance of food availability as part of regional food security, particularly in Pekanbaru City. Efforts to improve food availability require synergy among Regional Government Organizations (OPDs) to ensure that policies are implemented in an integrated and effective manner. This study aims to analyze the synergy of the Pekanbaru City Government in improving food availability during the period 2021–2024. This research employs a qualitative method with a descriptive approach, utilizing purposive sampling interviews and documentation as data collection techniques. Data analysis was conducted through data reduction, data display, and conclusion drawing, using communication indicators (source-oriented and receiver-oriented communication) and coordination indicators (vertical and horizontal coordination) based on Mawar’s Synergy Theory. The findings indicate that institutional synergy has been established through the Mayor of Pekanbaru Decree Number 269 of 2024 concerning the Food Task Force Team of Pekanbaru City, supported by structured communication and both vertical and horizontal coordination among Regional Government Organizations. The Food Security Office acts as the leading sector, Bappeda integrates policies into regional planning documents, the Agriculture and Fisheries Office supports local food production, and the Central Statistics Agency (BPS) provides statistical data as a basis for policymaking. However, program implementation remains suboptimal due to budget constraints, limited human resources, and fluctuations in food production and supply. The study concludes that structural synergy has been established; however, strengthening resource harmonization, implementation consistency, and cross-sectoral program integration is necessary to achieve sustainable improvement in food availability. Keywords: Synergy, Food Security, Food Availability, Pekanbaru City